AGRONOMIC AND NITROGEN RECOVERY EFFICIENCY OF RICE UNDER TROPICAL CONDITIONS AS AFFECTED BY NITROGEN FERTILIZER AND LEGUME CROP ROTATION - M. M. Rahman; M. A. Islam; M. S. Azirun; A. N. Boyce (Journal of Animal and Plant Sciences, 2014)
Nitrogen is one of the most limiting factors for crop growth and productivity. However excessive application can lead to low N efficiency, higher production costs and environmental pollution. Winged bean, bush bean and rice crop plants were grown in a greenhouse with different rates of N fertilizer to estimate nitrogen agronomic efficiency (NAE), nitrogen recovery efficiency (NRE) and N uptake of rice when tropical two vegetable legume plants were grown in rotation with rice crop. Bush bean and winged bean were grown with N fertilizer at rates of 0, 2, 4 and 6 g m-2 preceding rice planting while rice was grown with N fertilizer at rates of 0, 4, 8 and 12 g m-2. Rice after winged bean grown with N at the rate of 4 g N m-2 achieved significantly higher NRE (30-33%) and NAE (24-27 g g-1) during both years. This prevailing effect of rice after winged bean is likely associated with higher biomass and N uptake during both years. Data from two growing seasons showed that rice after winged bean at the rate of 4 g m-2 can produce higher biomass and N accumulation of rice along with superior NRE and NAE values, which indicated a positive response for rice production without deteriorating soil fertility.
Keywords: Nitrogen efficiency; Nitrogen uptake; Legume residue